2019
DOI: 10.1016/j.tics.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Awake Reactivation of Prior Experiences Consolidates Memories and Biases Cognition

Abstract: Recent human fMRI studies provide evidence for spontaneous memory-related reactivation and hippocampal interactions during awake post-encoding time periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
174
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(190 citation statements)
references
References 163 publications
7
174
2
1
Order By: Relevance
“…Thus, the benefits of tDCS over the DLPFC might primarily stem from a direct modulation of synaptic plasticity processes within prefrontal areas, in itself favouring memory reorganization, eventually leading to improved recall accuracy. Secondly, as mentioned above, memory consolidation processes are thought to rely on the offline reactivation of learning-related neural activity (Peigneux et al, 2006;Tambini & Davachi, 2019;Wamsley, 2019). The reactivation of declarative, hippocampus-dependent memories through a dialogue between hippocampal and neocortical areas is possibly mediated by slow oscillatory activity at wake (Brokaw et al, 2016) like during sleep (Buzsaki, 1996).…”
Section: The Effects Of Tdcs On Memory Consolidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the benefits of tDCS over the DLPFC might primarily stem from a direct modulation of synaptic plasticity processes within prefrontal areas, in itself favouring memory reorganization, eventually leading to improved recall accuracy. Secondly, as mentioned above, memory consolidation processes are thought to rely on the offline reactivation of learning-related neural activity (Peigneux et al, 2006;Tambini & Davachi, 2019;Wamsley, 2019). The reactivation of declarative, hippocampus-dependent memories through a dialogue between hippocampal and neocortical areas is possibly mediated by slow oscillatory activity at wake (Brokaw et al, 2016) like during sleep (Buzsaki, 1996).…”
Section: The Effects Of Tdcs On Memory Consolidationmentioning
confidence: 99%
“…Supporting this hypothesis, animal and human studies evidenced the reinstatement of learningrelated brain activity during offline post-training periods, both at wake (Humiston, Tucker, Summer, & Wamsley, 2019;Peigneux et al, 2006;Tambini & Davachi, 2019;Wamsley, 2019) and during sleep (Jegou et al, 2019;Peigneux et al, 2004;Sara, 2010;Schonauer et al, 2017;Skaggs & Mcnaughton, 1996;Valdes, McNaughton, & Fellous, 2015). Although several studies reported better consolidation in declarative memory after sleep than wakefulness, mostly associated with the triggering of learning-related brain activity during slow wave sleep (SWS; for reviews see e.g.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such investigations are particularly difficult in humans, where signal detection must occur non-invasively, unless rare medical circumstances allow otherwise. How fast and anatomically localized neural dynamics can be studied using available neuroimaging techniques, in particular functional magnetic resonance imaging (fMRI), is therefore a major challenge for human neuroscience [for recent reviews, see e.g., 22, 23]. Here, we developed and experimentally validated a novel multivariate analysis method that allows to reveal the content and order of fast sequential neural events with anatomical specificity in humans using fMRI.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that post-learning neural processes play a critical role in consolidating new memories (Diekelmann & Born, 2010;McGaugh, 2000;Sasaki, Nanez, & Watanabe, 2010). One of the consolidation processes is the reemergence of the brain activities involved in the initial task during following wakefulness and sleep (Foster, 2017;Pfeiffer, 2017;Tambini & Davachi, 2019).…”
Section: Introductionmentioning
confidence: 99%